2001
DOI: 10.1111/j.1740-8261.2001.tb00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Appearance of Intra‐abdominal Granuloma Secondary to Retained Surgical Sponge

Abstract: This report describes two animals (one dog and one cat) with a retained surgical sponge. Both had nonspecific clinical signs. Clinical examination, ultrasonography and cytologic examination were used to identify an abdominal mass compatible with a granuloma. The lesions were surgically removed and confirmed histologically as granulomas secondary to a retained sponge. The ultrasonographic appearance was very similar in both animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…Forty‐two cases of retained surgical swabs have been reported in the veterinary literature (2 cats and 40 dogs) (Teague and others , Terrier and others , Pardo and others , Lamb and others , Bradley , Merlo and Lamb , Mai and others , Papazoglou and Patslkas , Tsioli and others , Miller and others , Deschamps and Roux , Frank and Stanley , Putwain and Archer , Haddad and others , Krimer and Duval , Rayner and others , Forster and others ). In these cases, swabs were most commonly left in the abdomen (81%) and most commonly following ovariohysterectomy (57%).…”
Section: Discussionmentioning
confidence: 99%
“…Forty‐two cases of retained surgical swabs have been reported in the veterinary literature (2 cats and 40 dogs) (Teague and others , Terrier and others , Pardo and others , Lamb and others , Bradley , Merlo and Lamb , Mai and others , Papazoglou and Patslkas , Tsioli and others , Miller and others , Deschamps and Roux , Frank and Stanley , Putwain and Archer , Haddad and others , Krimer and Duval , Rayner and others , Forster and others ). In these cases, swabs were most commonly left in the abdomen (81%) and most commonly following ovariohysterectomy (57%).…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous reports of retained surgical sponges in veterinary medicine, but the true incidence has not been determined 3–6 . Retained surgical sponges are also referred to as gossypibomas.…”
Section: Discussionmentioning
confidence: 99%
“…Typically the sponge incites an aseptic inflammatory reaction and formation of a granuloma around the foreign material. The interval between the surgery and discovery of the retained sponge varies from days to years 3 . Retained sponges can remain within the mesentery unassociated with abdominal organs or can be extruded into a hollow viscus, such as the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…To the authors' knowledge, there are only 19 cases of retained swabs reported in the ‘English language’ veterinary literature (Teague and others 1978, Pardo and others 1990, Lamb and others 1994, Merlo and Lamb 2000, Mai and others 2001, Frank and Stanley 2009, Putwain and Archer 2009, Haddad and others 2010, Krimer and Duval 2010, Rayner and others 2010). These reports are mainly focused on imaging of the foreign bodies (Lamb and others 1994, Merlo and Lamb 2000) although osteomyelitis (Teague and others 1978) and development of neoplasia (Pardo and others 1990, Miller and others 2006, Haddad and others 2010) was reported in several small animals, at the site of swab retention many years after original surgery.…”
mentioning
confidence: 99%